2015
DOI: 10.1007/s40496-014-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic and Tissue Tolerable Plasma Therapies as Alternatives to Antimicrobials to Control Pathogenic Biofilms

Abstract: The need for novel antimicrobial techniques has become critical for a number of reasons, including the emergence of resistant strains because of excessive prescription and misuse of antibiotics. The mouth is colonized by a large number of microorganisms. When these microorganisms are organized as biofilms they can contribute to chronic diseases in the human population, such as dental caries, candidiasis, and periodontal disease. Hence, alternative antimicrobial approaches have risen to facilitate the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…For example, several research groups compared the relative performance of CAP in the eradication of bacterial biofilms and embedded bacteria with aPDT [ 76 , 141 , 142 , 143 , 144 ]. The results of these comparative studies showed that although CAP significantly reduced bacterial biofilms and inhibited their formation, the overall relative performance was in par or less than that of aPDT, in line with conclusions made by an earlier comparative review [ 145 ]. Therefore, the researchers recommended further improvement of the CAP combination with aPDT.…”
Section: Combination With Cold Atmospheric Pressure Plasma Therapysupporting
confidence: 88%
“…For example, several research groups compared the relative performance of CAP in the eradication of bacterial biofilms and embedded bacteria with aPDT [ 76 , 141 , 142 , 143 , 144 ]. The results of these comparative studies showed that although CAP significantly reduced bacterial biofilms and inhibited their formation, the overall relative performance was in par or less than that of aPDT, in line with conclusions made by an earlier comparative review [ 145 ]. Therefore, the researchers recommended further improvement of the CAP combination with aPDT.…”
Section: Combination With Cold Atmospheric Pressure Plasma Therapysupporting
confidence: 88%
“…In a world-first and groundbreaking study, the combination of CAP and PDT against skin and wound pathogens has been reported to have synergistic enhancement of efficacy in vitro [ 174 ]. The combination of PDT with CAP has been scantily reviewed [ 175 ]. However, research reports of novel innovations that combine CAP with PDT have appeared in the literature.…”
Section: Combinations Of Photodynamic Therapy With Cold Atmospheric P...mentioning
confidence: 99%